Governing the inner "periphery." Spatial security governance of the Highlands in Papua New Guinea since the colonial period. (March 2022) - Distler, Werner
Abstract: Specific regions and places are considered particular threatening and dangerous by state authorities. There, the state regularly enacts security in harsh and violent ways. In this article, I develop a pragmatic spatial framework, inspired by and combining elements from post-statist geography and Critical Security Studies, to explain patterns of spatial security governance in regions with competing local authorities and regular violence. I particularly argue for more historical analysis on the emergence and legacies of spatial security governance to understand its persistence and consequences. I illustrate the framework with an empirical investigation of the spatial security governance of the Highland regions in Papua New Guinea, and its role as a dangerous inner "periphery" for the central state since the late colonial period. The patterns of security governance in the Highlands, like the declaration of emergency zones in case of regional warfare, the use of violent punitive expeditions by mobile forces, accompanied by a securitizing discourse, have remained remarkably similar. While the post-colonial state aimed at a break with the colonial past, the spatial security governance of the Highlands has remained an important source for the legitimization of state rule and state formation. Governing the inner "periphery" is constructed as the responsibility of the state, which has been historically entangled in the "violent geographies" in the Highlands.